e) x ∈ (-7;12].
f) x ∈ [-4;6].
g) x ∈ (-9; -5).
h) х ∈ (1;4).
Пошаговое объяснение:
e) x≤12;
-x<7; [*(-1)] меняем знак неравенства на противоположный
x>-7;
ответ: x ∈ (-7;12].
***
f) Решаем первое неравенство:
2x-x≥ -1 - 3;
x≥-4;
Решаем второе неравенство:
5x-x≤2+22;
4x≤24;
x≤6;
ответ: x ∈ [-4;6].
***
g) 6x+4>5x-5;
6x-5x>-5-4;
x>-9;
6x+9>7x+14;
6x-7x>14-9;
-x>5; [*(-1)] меняем знак неравенства на противоположный
х<-5;
ответ: x ∈ (-9; -5).
***
h) x/3 - x/4<x/6 - 1;
x/3-x/4-x/6< -1;
-x/12<-1; [*(-1)] меняем знак неравенства на противоположный
x>1;
6-x/2>3+x/4;
-x/2-x/4>3-6;
- 3/4x>-3;
-x> -3 : 3/4;
-x> -3*4/3;
-x>-4; [*(-1)] меняем знак неравенства на противоположный
x<4;
ответ: х ∈ (1;4).
х = 36 : (-9) х = - 2,4 : 0,6 х = - 5,4 : (-1,8)
х = - 4 х = - 4 х = 3
1/7х = - 5/14 - 5/6х = - 1/7 - 2 5/6х = 17/16
х = - 5/14 : 1/7 х = - 1/7 : (-5/6) - 17/6х = 17/16
х = - 5/14 * 7/1 х = - 1/7 * (-6/5) х = 17/16 : (-17/6)
х = - 5/2 х = 6/35 х = 17/16 * (-6/17)
х = - 2 1/2 х = - 3/8
(- 28,6 : 57,2 - 26,8 : (-1,34)) * (-3,1) = 63,55
1) - 28,6 : 57,2 = - 0,5
2) 26,8 : (-1,34) = - 20
3) - 0,5 - 20 = - 20,5
4) - 20,5 * (-3,1) = 63,55